Plant-Growth Promotion of Argentinean Isolates of Azospirillum brasilense on Rice (Oryza sativa L.) Under Controlled and Field Conditions - Puente, Mariana Laura (2013)
Azospirillum sp. has been shown to be a valuable resource to stimulate the growth and yield of diverse crop species. However, successful plant growth promotion (PGP) upon inoculation often depends on combining proper bacterial strains and plant genotypes. In this study, we isolated and characterized four new A. brasilense strains from diverse regions of Argentina and evaluated their PGP effect on a rice commercial local genotype under both controlled and field conditions. Under controlled conditions, most of the Azospirillum strains analyzed promoted plant growth, as evidenced by a significant increase in shoot height and root length and in some cases in dry weight. Strains Az24 and Az72 were the most effective. Unexpectedly, strain Az23, which was recovered from a rice productive field was a poor growth promoter of rice seedlings. Under field conditions, none of the parameters measured were statistically different from those of the control group. This lack of statistical significance might be attributed to the high dispersion of the data, which is expected in field experiments. In sum, our results suggest that Azospirillum promotes rice growth as a result of a nonspecific plant-bacterium interaction.